The Influence of Time Management, Work Motivation, and Work Environment on Employee Work Productivity - Danda, Made; Subiyanto, Didik; Purnamarini, Tri Ratna (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the influence of time management, work motivation, and work environment on employee productivity at the Yogyakarta Employment Social Security Office. Using a quantitative approach with a survey of 40 respondents and multiple linear regression analysis via SPSS 23, the results show that time management and work motivation positively and significantly impact productivity, while the work environment does not. These findings offer strategic insights for enhancing productivity through effective time use and motivational improvements in public organizations undergoing digital transformation. Keywords: Time Management, Work Motivation, Work Environment, Work Productivity, Public Organization, Employee Performance, Digital Transformation, Human Resource Management